Vitamin D Reverts the Exosome-Mediated Transfer of Cancer Resistance to the mTOR Inhibitor Everolimus in Hepatocellular Carcinoma - Negri, Mariarosaria; Amatrudo, Feliciana; Gentile, Annalisa; Patalano, Roberta; Montò, Tatiana; de Angelis, Cristina; Simeoli, Chiara; Pirchio, Rosa; Auriemma, Renata Simona; Colao, Annamaria; Pivonello, Rosario; Pivonello, Claudia (Frontiers in Oncology, 2022)
Several multi-kinase inhibitors were widely tested as potential first- or second-line therapy in patients with advanced hepatocellular carcinoma (HCC). However, acquired drug resistance limits their clinical efficacy. Exosomes are microvesicles secreted by tumour and stromal cells that participate in many biological processes, including drug resistance. The current study evaluated the capability of exosomes derived from everolimus (EVE)-resistant HCC cells in inducing drug resistance in parental human HCC cells and the effect of 1,25(OH)2Vitamin D (VitD) treatment in restoring the EVE sensitivity. The internalization of exosomes from EVE-resistant (EveR) cells into parental cells conferred the transmission of aggressive phenotype by promoting the transition of epithelial to mesenchymal phenotype, as demonstrated by immunofluorescence, and the acquisition of EVE resistance, as demonstrated by cell proliferation and colony formation assays. Moreover, the internalization of exosomes from EveR into parental cells induced deregulation of the mTOR pathway mainly by triggering the activation of the serine/threonine protein kinase Akt, involved in the cellular survival pathway, as demonstrated by western blot analysis. Interestingly the treatment with VitD prevented exosome-induced EVE resistance in HCC cells, significantly inhibiting cell proliferation but also partially reducing colony and size number when combined with EVE compared with control. In conclusion, the results of the current study demonstrated that exosomes derived from EveR cells could induce EVE resistance in EVE sensitive HCC cells and that VitD can revert the exosome-induced EVE resistance by re-sensitizing to EVE treatment.